Efektivitas Hak-Hak Warga Negara dalam Sistem Administrasi Publik: Studi Kasus pada Pelayanan Publik di Kabupaten Merauke - Syahrabudin Husein Enala; Syahruddin; Umiyati Haris (PAPSEL Research and Consulting, 2024)
This research aims to evaluate the effectiveness of fulfilling citizens' rights within the public administration system in Merauke Regency, South Papua. The focus of the study is on services related to civil administration, healthcare, education, and licensing, as well as the challenges encountered in accessing these services, particularly in remote rural areas. The research employs a descriptive qualitative method, collecting data through in-depth interviews, field observations, and document studies. The informants include citizens using public services, government officials, and community leaders. The findings reveal a significant disparity in access and quality of services between urban and rural areas in Merauke. Residents in remote areas face various challenges, such as limited infrastructure, a shortage of healthcare workers and teachers, as well as geographical barriers that delay the fulfillment of their basic rights, particularly in healthcare, education, and civil administration services. The digitization of services is also uneven, as limited internet access in rural areas hampers licensing services. Based on these findings, the study proposes a new theory, Geographically Adaptive Public Service, which emphasizes the importance of adapting public services to local geographical and socio-cultural conditions. This theory offers a more flexible and innovative approach to public service delivery in remote areas, aiming to ensure the equitable fulfillment of citizens' rights. In conclusion, service innovation and a more adaptive approach are needed to improve the quality of public services in Merauke Regency, particularly in reaching communities in hard-to-access areas.